Combatting maritime offences in Malaysia: an analysis of legal and procedural loopholes - Hamid, Abdul Ghafur@Khin Maung Sein (2014)
Malaysian waters are prone to armed robberies at sea or other maritime attacks. At the same time Malaysian vessels are vulnerable to piratical attacks on the high seas. This paper first of all examines the seriousness of maritime threats against Malaysia or Malaysian interests. It then carries out an in-depth analysis of the procedural and substantive criminal laws of Malaysia in order to shed light on the legal vacuum, if any, in the Malaysian laws. The paper finds that piracy or other maritime offences are not offences under the Penal Code, the primary substantive criminal law in Malaysia. Moreover, section 2 of the Penal Code limits its scope to offences committed within Malaysia only and the limited extraterritorial offences under section 4 do not include piracy or other maritime offences. Although the Courts of Judicature Act 1964 allows the High Court to exercise jurisdiction over piracy jure gentium committed on the high seas, there is no substantive law which criminalizes piracy. Two possible approaches are proposed to fill the legal vacuum: to revise the Penal Code by adding a new Chapter on Maritime Offences or to adopt a special law to be known as “Maritime Offences Act.” This paper advocates the second approach for the obvious reason that maritime offences needs special treatment.